Systematics and distribution of the giant fossil barn owls of the West Indies (Aves: Strigiformes: Tytonidae) - Suárez, William; Olson, Storrs L. (Zootaxa, 2015)
After reviewing the systematics and distribution of the extinct West Indian taxa of Tytonidae (Tyto) larger than the living barn owl Tyto alba (Scopoli), we reached the following conclusions: (1) the species T. ostologa Wetmore (1922) is the only giant barn owl known so far from Hispaniola; (2) T. pollens Wetmore (1937) was a somewhat larger and even more robust representative of T. ostologa known from the Great Bahama Bank and Cuba; (3) the very rare species T. riveroi Arredondo (1972b) is here synonymized with T. pollens; (4) the smallest taxon of these giant barn owls is T. noeli Arredondo (1972a), which is widespread and abundant in Quaternary deposits of Cuba and is here reported for the first time from two cave deposits in Jamaica; (5) the only large barn owl named so far from the Lesser Antilles is T. neddi Steadman & Hilgartner (1999), which is here synonymized with T. noeli; (6) a new taxon from Cuba, T. cravesae new species, which in size approached the linear dimensions of T. ostologa, is named and described herein.